2008
DOI: 10.1021/nl072304q
|View full text |Cite
|
Sign up to set email alerts
|

Non-Brownian Diffusion of Membrane Molecules in Nanopatterned Supported Lipid Bilayers

Abstract: Molecules associated with the outer surface of living cells exhibit complex, non-Brownian patterns of diffusion. In this report, supported lipid bilayers were patterned with nanoscale barriers to capture key aspects of this anomalous diffusion in a controllable format. First, long-range diffusion coefficients of membrane-associated molecules were significantly reduced by the presence of the barriers, while short-range diffusion was unaffected. Second, this modulation was more pronounced for large molecular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…In that study, glass substrates were patterned with 50-nm wide Cr lines with 125-nm or 250-nm spacing and sub-50-nm gaps interspersed throughout the Cr barriers (Figure 7a). 77 In fluorescence recovery after photobleaching experiments, it was demonstrated that the longrange diffusion of the lipids on these substrates was significantly reduced, whereas the short-range diffusion was preserved. Furthermore, the cholera toxin subunit B/GM 1 complexes were less likely to cross the nanoscale barriers than the individual lipid molecules.…”
Section: Lipid-nanostructure Hybrids For Modulation Of Lipid Membranementioning
confidence: 97%
“…In that study, glass substrates were patterned with 50-nm wide Cr lines with 125-nm or 250-nm spacing and sub-50-nm gaps interspersed throughout the Cr barriers (Figure 7a). 77 In fluorescence recovery after photobleaching experiments, it was demonstrated that the longrange diffusion of the lipids on these substrates was significantly reduced, whereas the short-range diffusion was preserved. Furthermore, the cholera toxin subunit B/GM 1 complexes were less likely to cross the nanoscale barriers than the individual lipid molecules.…”
Section: Lipid-nanostructure Hybrids For Modulation Of Lipid Membranementioning
confidence: 97%
“…Tsai et al [22] proposed that anomalous diffusion can be characterised by two diffusion coefficients, one describes short-range motion within an individual compartment and the other, smaller, effective diffusion coefficient is associated with long-range motion over many barriers. Specifically, molecular motion parallel to the barriers is unhindered, in the absence of any impact of the barriers on local membrane mobility, long-range diffusion coefficients measured in this direc- …”
Section: Resultsmentioning
confidence: 99%
“…[15] This concept of the molecular filtering effect was recently confirmed by the use of a single nanogate. [19,21] In 2008, Tsai et al [22] designed arrays of nanoscale linear barriers patterned on glass substrates to capture key aspects of anomalous diffusion. They found that diffusion coefficients of the molecule depended on barrier spacing, gap size and barrier material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studying lipid diffusion around nanofabricated channels 90,95 and nanogates 66 has provided insights of membrane diffusion on complex surfaces. Carefully designed surface patterns may be applied for selective sorting of membrane components based on molecular mobility, size, or charge.…”
Section: Restricting Membrane Diffusionmentioning
confidence: 99%